Human–nature connection: a multidisciplinary review - Ives, Christopher D.; Giusti, Matteo; Fischer, Joern; Abson, David J.; Klaniecki, Kathleen; Dorninger, Christian; Laudan, Josefine; Barthel, Stephan; Abernethy, Paivi; Martín-López, Berta; Raymond, Christopher M.; Kendal, Dave; et al. (Elsevier, 2017)
In sustainability science calls are increasing for humanity to (re-)connect with nature, yet no systematic synthesis of the empirical literature on human–nature connection (HNC) exists. We reviewed 475 publications on HNC and found that most research has concentrated on individuals at local scales, often leaving ‘nature’ undefined. Cluster analysis identified three subgroups of publications: first, HNC as mind, dominated by the use of psychometric scales, second, HNC as experience, characterised by observation and qualitative analysis; and third, HNC as place, emphasising place attachment and reserve visitation. To address the challenge of connecting humanity with nature, future HNC scholarship must pursue cross-fertilization of methods and approaches, extend research beyond individuals, local scales, and Western societies, and increase guidance for sustainability transformations.